National survey of Research and Development in Malaysian 2016 - Hashim, Junaidah; Islam, Rafikul; Sidek, Shahrul Na'im; Abdul Rahman, Rozailin; Zakaria, Norshuhaida; Rahman, Mahbubar; Rosli, Nazreen; Abu Hanifah, Rabiatuladawiah (Ministry of Science, Technology and Innovation (MOSTI), 2018)
Malaysia's R&D landscape has grown tremendously over the last decade. Malaysia has put serious efforts in improving its research, development and innovation activities. As a result, Malaysia has managed to stand at par with many developed countries with regard to its competitiveness through adopting science and technology policies and taking significant actions to increase the research and development infrastructure in the past deeades. The country has also witnessed a marked increase in a number of R&D activities. In every cycle of Malaysia Plan, emphasis is given to R&D. During the Tenth Plan, series of actions to strengthen ecosystem were undertaken, among others include shaping a supportive ecosystem by creating enabling environment for stakeholders to carry out innovation activities, and providing funds for research development and commercialisation (R&D&C) initiatives. This is due to the fact that innovation is crucial for the development agenda to increase productivity and improve competitiveness into new wealth for the nation. For the Eleventh Plan, Malaysia has outlined series of efforts to be undertaken to translate innovation into new wealth for the nation. Strategies will be targeted at two levels -the enterprise and society with the aim of translating innovation to wealth. One of the measures of a developed country is the ability to produce quality research that can benefit the entire nation and improve the national gross domestic product. This is what the National Survey of R&D seeks to measure and the survey has been conducted by the Malaysian Science and Technology Information Centre (MASTIC) since 1994. The National Survey of R&D 2016 was based on the financial year of 2015 unless specified otherwise. The data was collected between 2015 and 2016 utilizing both primary and secondary data. The survey comprised of Business Enterprises (BEs ), Higher Learning Institutions (HLis) and Government and Research Institutes (GRis). Unfortunately, no NonGovernmental Organisations (NGOs) were included in the survey as they did not conduct R&D based on the parameters ofFrascati Manual, 2015.